A Countercyclical Training Programme for Canada - Newton, Keith (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1971)
The author examines the current interest in the potential role of manpower policy as a stabilizing instrument and, more specifically, the contribution of one component : adult training programmes